K-State Turfgrass Research 1999 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 1999)
It might be a simple question, such as "Which tall fescue cultivars are best suited for use on lawns?" or possibly a more complicated one, such as "What causes the quality of my bentgrass greens to decline in July?" Answers to these questions and many others are contained in this 1999 edition of Turfgrass Research.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 836; Kansas Agricultural Experiment Station contribution; no. 99-458-S; Turfgrass; Pest management; Environmental stress; Buffalograss; Bluegrass; Tall Fescue; Bermudagrass; Zoysiagrass